Commoditization of God in religion: Marketing ‘Pentecostalism’ in the Nigerian public space - Afolabi, Oluwaseun O. (Journal of Pentecostal and charismatic Christianity, 2024)
Religion cannot thrive on its own without the use of a Supreme Being or the use of God as a symbol of the supernatural on the society. In Nigerian society, religion has become a major occupation and most sought after by the people. This paper explores the invaluableness of God in religion through the use of marketing and how Pentecostal practitioners commodify God in the public space. This paper argues that God in religion has been converted into services and marketable product in the Nigerian public space, which leads to ‘rivalry’ among Pentecostal churches to gain mass appeal, membership, promotion of church and theological affiliations, and the creation of businesses, which is largely fuelled by massive socio-economic and political disorder in the country.